(untitled) (Journal of the College of Basic Education, 2023)
The current research aims at identifying the Woods model that helps students build knowledge themselves by linking their past knowledge with subsequent knowledge, thus helping the learner develop his mental skills through prediction, observation and interpretation in the form of collaborative groups, Especially when the emergence of strategies and models and modern methods called attention to the student rather than the preservation of study materials, which is the transfer of the educational process from relying on the lesson to rely on the student himself in the process of learning with the participation of the teacher, especially as the age we live is p In the face of these changes, the education system has to keep abreast of this development, including the knowledge of the Woods model, so that learners can cope with the various changes and how to adapt to them. .